Geothermal Pipeline - Geo-Heat Center (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1992)
The International Conference on the Industrial Uses of Geothermal Energy was held in Reykjavik, Iceland, 02-04 September 1992. Approximately 200 people attended the conference, and 70 papers were presented. The purposes of the conference were to introduce the possibilities of using geothermal energy in industry, to collect experience and knowledge, and to gain an overview of the current status in the world in this field